Підвищення надійності експлуатації електротехнічного перетворювача - Мазуренко, Ольга Олександрівна; Самсонов, Валерій Васильович; Хлобистова, Ольга Андріївна; Угляренко, В. П. (My University, 2013)
У статті показано, що для забезпечення надійності електротехнічних перетворювачів шляхом запобігання відмов варто використовувати діагностичний комплекс, в програмному забезпеченні якого враховані дані попередніх досліджень конкретного електротехнічного перетворювача. Використання такого діагностичного комплексу дозволить суттєво зменшити збитки від перебоїв в електропостачанні. The paper shows that, to ensure reliable operation of electrical converters require the use of a diagnostic facility to prevent the emergence and development analysis failures. Because of the complexity of the design, every single electrical converter is an individual, so this diagnostic system must use basically correct standard, compiled individually for each individual machine on the basis of tests and studies of changes in states machine since its introduction into service. individuality standard plays a key role in determining the true technical state of the machine, which will significantly improve the performance reliability characteristics of electrical transformers and significantly reduce the damage caused by power outages and population sectors of the economy.
Keywords: електропостачання; діагностичний комплекс; електромеханічний перетворювач; power supply; diagnostic equipment; electromechanical converter; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки